2005
DOI: 10.1086/432713
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Distribution of SDSS Satellite Galaxies: Planar (Not Polar) Alignment

Abstract: The distribution of satellite galaxies relative to isolated host galaxies in the Sloan Digital Sky Survey (SDSS) is investigated. Host-satellite systems are selected using three different methods, yielding samples of ∼ 3300, ∼ 1600, and ∼ 950 satellites. In the plane of the sky, the distributions of all three samples show highly significant deviations from circular symmetry (> 99.99%, > 99.99%, and 99.79% confidence levels, respectively), and the degree of anisotropy is a strong function of the projected radiu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

26
202
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(228 citation statements)
references
References 35 publications
26
202
0
Order By: Relevance
“…Although the alignments between the host shapes and the satellite locations have been supported by several observational studies (e.g., Brainerd 2005;Yang et al 2006;Azzaro et al 2007;Bailin et al 2008;Agustsson & Brainerd 2010, no direct observational evidence was found for the preferential alignments of the satellite infall directions with the minor principal axes of the velocity shears, nor for the strong crosscorrelations between the velocity shear field smoothed on different scales. Very recently, Lee et al (2014) have found observational evidence for the alignments between the infall directions of the satellite galaxies and the minor principal axes of the local velocity shear tensors.…”
Section: Introductionmentioning
confidence: 88%
“…Although the alignments between the host shapes and the satellite locations have been supported by several observational studies (e.g., Brainerd 2005;Yang et al 2006;Azzaro et al 2007;Bailin et al 2008;Agustsson & Brainerd 2010, no direct observational evidence was found for the preferential alignments of the satellite infall directions with the minor principal axes of the velocity shears, nor for the strong crosscorrelations between the velocity shear field smoothed on different scales. Very recently, Lee et al (2014) have found observational evidence for the alignments between the infall directions of the satellite galaxies and the minor principal axes of the local velocity shear tensors.…”
Section: Introductionmentioning
confidence: 88%
“…It is argued, based on simulations, that the preferred accretion direction of satellite halos toward the host halo along the filaments is largely responsible for the BCG alignment (Tormen 1997;Vitvitska et al 2002;Knebe et al 2004;Zentner et al 2005;Wang et al 2005). The detection of this alignment from real data has been reported by many teams (Sastry 1968;Austin & Peach 1974;Dressler 1978;Carter & Metcalfe 1980;Binggeli 1982;Brainerd 2005;Yang et al 2006;Azzaro et al 2007;Wang et al 2008;Siverd et al 2009;Niederste-Ostholt et al 2010), though non-detections of this alignment were also reported (Tucker & Peterson 1988;Ulmer et al 1989). For the satellite alignment, tidal torque is thought to play a major role in its formation (Ciotti & Dutta 1994;Ciotti & Giampieri 1998;Kuhlen et al 2007;Pereira et al 2008;Faltenbacher et al 2008;Pereira & Bryan 2010).…”
Section: Introductionmentioning
confidence: 96%
“…In particular, recent studies of galaxies in the Sloan Digital Sky Survey (SDSS; York et al 2000) have revealed that satellite galaxies are preferentially distributed along the major axis of the central galaxies (Brainerd 2005;Yang et al 2006;Azzaro et al 2007;Faltenbacher et al 2007Faltenbacher et al , 2009) and tend to be preferentially oriented toward the central galaxy (Pereira & Kuhn 2005;Agustsson & Brainerd 2006;Faltenbacher et al 2007). These studies were mostly limited to the local universe and intermediate-to-small scales (less than a few tens of Mpc).…”
Section: Introductionmentioning
confidence: 99%